SENSITIVITY OF GRAPHENE OXIDE COATED TAPERED NO-CORE FIBRE SENSOR FOR URIC ACID DETECTION - Zaini, M.I.A.; Daud, Suzairi; Noorden, A.F.A. (Journal of Engineering and Technology (JET), 2024)
This paper analyses the development, progress, and evaluation of a sensor system, which mainly consists of tapered no-core fibre (TNCF) for detecting uric acid (UA). To augment the capability of TNCF diameter, different powers of CO2 laser were used for creating the optical-based refractive index sensor. This action will allow for better interaction with the surrounding samples, improving the sensitivity. The sensing region was fixed to improve the sensitivity with a coating of graphene oxide (GO) solution. Experimental findings showed that the TNCF-GO sensor exhibited a higher sensitivity value at 0.00782 ± 0.00049 nm/µM, while NCF-GO sensor sensitivity only at 0.00447 ± 0.00019 nm/µM and NCF sensor sensitivity only at 0.00387 ± 0.00027 nm/µM. The TNCF-GO sensor demonstrated better performance compared to the others. This research improves the development of a susceptible and effective sensor for UA detection, especially in biomedical health diagnostics.